Pengaruh Keputusan Investasi, Likuiditas, Profitabilitas Terhadap Nilai Perusahaan (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2016-2018) - Fanny Putri Ramadhani; N Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to determine the effect of independent variables, namely investment decisions, liquidity, profitability on the dependent variable, namely the value of the company in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2018. The population used in this study is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2016-2018 period. The method for sampling uses purposive sampling based on predetermined criteria. The number of samples is 71 manufacturing companies. The data in this study use multiple linear regression, classic assumptions and hypothesis testing.The results of this study as a whole or simultaneous independent variables namely investment decisions, liquidity, profitability have a positive and significant effect on firm value. Partially, investment decisions have a positive and significant effect on firm value, liquidity has a negative and significant effect on firm value and profitability has a positive and significant effect on firm value.Keywords: investment decisions, liquidity, profitability, firm value